Intestinal Bacteria Interplay With Bile and Cholesterol Metabolism: Implications on Host Physiology - Molinero, Natalia; Ruiz, Lorena; Sánchez, Borja; Margolles, Abelardo; Delgado, Susana (Frontiers in Physiology, 2019)
Bile is a biological fluid synthesized in the liver, mainly constituted by bile acids and cholesterol, which functions as a biological detergent that emulsifies and solubilizes lipids, thereby playing an essential role in fat digestion. Besides, bile acids are important signalling molecules that regulate key functions at intestinal and systemic levels in the human body, affecting glucose and lipid metabolism, and immune homeostasis. Apart from this, due to their amphipathic nature, bile acids are toxic for bacterial cells and thus, exert a strong selective pressure on the microbial populations inhabiting the human gut, decisively shaping the microbial profiles of our gut microbiota, which has been recognised as a metabolic organ playing a pivotal role in host health. Remarkably, bacteria in our gut also display a range of enzymatic activities capable of acting on bile acids and, to a lesser extent, cholesterol. These activities can have a direct impact on host physiology as they influence the composition of the intestinal and circulating bile acid pool in the host, affecting bile homeostasis. Given that bile acids are important signalling molecules in the human body, changes in the microbiota-residing bile biotransformation ability can significantly impact host physiology and health status. Elucidating ways to fine-tune microbiota-bile acids-host interplay are promising strategies to act on bile and cholesterol-related disorders. This manuscript summarizes the current knowledge on bile and cholesterol metabolism by intestinal bacteria, as well as its influence on host physiology, identifying knowledge gaps and opportunities to guide further advances in the field..